ANALISIS LOYALITAS KARYAWAN DARI PERSPEKTIF KEPUASAN KERJA PADA KARYAWAN TELLER PT BPD DIY CABANG SENOPATI - sugiyanti sugiyanti (UPAJIWA, 2020)
The research was conducted to test variable influence, compensation , workplace and career development on employee loyalty them through job satisfation at PT BPD DIY Branch Senopati. This study using the independent variable, compensation ,workplace, and career development, the dependent variable, employee loyalty and the variable job satisfaction is intervening. Sampling technique used is census. Namely research technique census was taken of all subjects or population. Sample were using the procedure 36 koesioner data collection. The analysis used the technique analysis 18.0. spss a walker And smartpls 3.2.8. The hypothesis testing in research, it can be concluded that compensation and workplace have had a positive impact on the job satisfaction and employee loyalty. But compensation not significantly and work place to the job satisfaction and employee loyalty. To career debelopment significant work on the job satisfaction and insignificant on employee loyalty. For job satisfaction have had a positive impact and significant employee loyalty. Keywords: Compensation ,work environment, career development, job satisfaction and employee loyalty